5 - Gender Revolution Prospects in Nigeria: Implications for Marriage Timing and Fertility - Onipede Wusu,; Olaide A. Adedokun, (African Sociological Review, 2017)
We hypothesise that the prospects of gender revolution (GR) is rising in Nigeria and may be swaying marriage timing and fertility. The 1990 and 2013 NDHS data and 45 in-depth interviews were analysed. The analysis suggests that the prospects for the emergence of GR increased between 1990 and 2013. Women with high GR status positively predicted marriage timing in 2013 as against the inconsistent association observed in 1990. Similarly, high GR status negatively predicted children ever born (CEB) in 2013. Also, qualitative data suggest a general preference for completing education and participating in labour market before marriage among women. The findings suggest that as the proportion of women with improved GR status increases across Nigeria, delayed marriage is likely to soar and sustainable fertility decline achieved. Social policy to accelerate female education and labour force participation along with realistic economic recovery strategies are therefore of critical importance.